Analysis and Prognosis of Failures in Intelligent Hybrid Systems Using Bioengineering: Gear Coupling - Roberto Outa; Fabio Roberto Chavarette; Vishnu Narayan Mishra; Aparecido Carlos Gonçalves; Adriana Garcia; Sandro da Silva Pinto; Laxmi Rathour; Lakshmi Narayan Mishra (The Journal of Engineering and Exact Sciences)
This work is of multidisciplinary concept, whose development is difficult to perform. Considering also that, in one of the steps, the similarity between the FRF of the vibration and acoustic signal is demonstrated. The objective of this work is the analysis and prognosis of the progression of failures of a pair of gears using the artificial immune system (AIS) of negative selection. In order to have this condition met, during the development of this work, the Wiener filter technique, the vibration and acoustic signal analysis (FRF), the application of negative selection AIS techniques for classification and grouping of signals were applied. The final result successfully demonstrates the effectiveness of the development process of this work and the robustness of the negative selection AIS algorithm.